2019
DOI: 10.1109/tii.2018.2867626
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of an Autonomous Hybrid Renewable Energy System Using Reformed Electric System Cascade Analysis

Abstract: This paper presents reformed electric system cascade analysis (RESCA) technique for optimization of hybrid renewable energy system (HRES) comprising of wind energy conversion system (WECS), photo-voltaic system (PV), battery energy storage system (BESS) and non-intermittent source (NIS). Optimization constraints of final excess energy (FEE), energy generation ratio (EGR), cost of energy (COE), net present cost (NPC) and renewable energy fraction (REF) are considered for the optimization of the system. This opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(34 citation statements)
references
References 36 publications
0
34
0
Order By: Relevance
“…Among the various topics associated with HESs, optimal sizing of the components is an important subject for researchers to explore the optimal design of the system [34]. Such a decision‐making problem can be accomplished to achieve a range of objectives: decreasing the costs of HES, reducing the air pollution, increasing the reliability, boosting the customer satisfaction, decreasing the excess energy in the system etc.…”
Section: Introductionmentioning
confidence: 99%
“…Among the various topics associated with HESs, optimal sizing of the components is an important subject for researchers to explore the optimal design of the system [34]. Such a decision‐making problem can be accomplished to achieve a range of objectives: decreasing the costs of HES, reducing the air pollution, increasing the reliability, boosting the customer satisfaction, decreasing the excess energy in the system etc.…”
Section: Introductionmentioning
confidence: 99%
“…Simulation results showed that MOCSA found well‐distributed and widely spread non‐dominated solutions in the Pareto front. Singh and Bansal [32] used the reformed electric system cascade analysis to optimise a hybrid energy system. In [33], a standalone hybrid energy system composed of wind farm, energy storage system and local consumer was considered.…”
Section: Introductionmentioning
confidence: 99%
“…To mitigate the power quality issues, energy storage systems are often used in synchronicity with the wind-diesel system to maintain an instant balance between generation and demand [5]. Integration of energy storage system enhances the robustness of the system, making it more resistant to disturbances [3,6,7]. Energy storage devices with fast response time, high ramp rates and high cyclic efficiency are well suited for mitigating the power fluctuations that are generated due to stochastic nature of wind power.…”
Section: Introductionmentioning
confidence: 99%